Count on us : American women in the military - Nathan, Amy (Washington, D.C. : National Geographic, 2004)
Reviews the history of American women's involvement in the Armed Forces from the Revolutionary War to the present
Introduction / Remembered at last -- Revolutionary War 1775 - 1783 -- Civil War 1861 - 1865 -- World War I 1917 - 1918 -- World War II 1941 - 1945 -- Korean War 1950 - 1953 -- Vietnam War 1959 - 1975 -- Persian Gulf War 1990 - 1991 -- Keeping the peace 1990s -- Afghanistan, Iraq, & beyond -- Resources -- Acknowledgments -- Index
Includes bibliographical references (p. 86-87) and index
Keywords: Women soldiers -- United States -- Juvenile literature; United States -- Armed Forces -- Women -- Juvenile literature